Real-time cell analysis of the cytotoxicity of the components of orthodontic acrylic materials on gingival fibroblasts - Öztürk, Firat; Malkoc, Siddik; Ersöz, Mustafa; Hakki, Sema S.; Bozkurt, Buket S. (American journal of orthodontics and dentofacial orthopedics, 2011)
The aim of this study was to evaluate the cytotoxicity of 3 orthodontic acrylic materials and 2 manipulation methods. The orthodontic acrylic materials Orthocryl EQ (Dentaurum, Ispringen, Germany), Orthoplast (Vertex Dental, Zeist, The Netherlands), and O-80 (Imicryl, Konya, Turkey) were prepared with 2 polymerization methods (doughing and spray on). Totally, 60 cylinders (5 × 2 mm), fabricated by using a different acrylic and method, were divided into 6 groups. Gingival fibroblasts were isolated from gingival connective tissue of systemically healthy subjects. Materials were incubated in Dulbecco's modified eagle's medium culture medium (Biological Industries, Beit Haemek, Israel) for 72 hours according to ISO 10993-5 standards (surface area to volume ratio of the specimen to cell-culture medium: 3 cm 2/mL). Gingival fibroblasts were maintained with Dulbecco’s modified eagle medium containing 10% fetal bovine serum. A real-time cell analyzer (RT-CES, xCELLigence; Roche Applied Science, Mannheim, Germany, and ACEA Biosciences, San Diego, Calif) was used to evaluate cell survival. After seeding 200 μL of the cell suspensions into the wells (20,000 cells/well) of the E-plate 96, gingival fibroblasts were treated with bioactive components released by the acrylic materials (1/1 and 1/2 dilutions) and monitored every 15 minutes for 121 hours. For the proliferation experiments, the statistical analyses used were 1-way analysis of variance (ANOVA) and Tukey-Kramer multiple comparisons tests. There was no significant difference between the cell indexes of the control and study groups for the 1/1 and 1/2 dilutions at 21 and 32 hours. When evaluated at 68 hours, all 1/2 dilutions of acrylic materials showed statistically insignificant differences ( P >0.05) except for Orthoplast ( P <0.05). But all acrylic materials were different from the control group in the 1/1 dilutions ( P <0.001). At 121 hours, all test groups were significantly different from the untreated control group ( P <0.001). The results indicate that the long cycle increased the cytotoxicity of the tested materials, and there was no significant difference between the spray-on and doughing methods on cytotoxicity.